Polycarbonate Urethane Mesh: A New Material for Pelvic Reconstruction. Issue 2 (February 2021) - Bickhaus, Jennifer A.; Fraser, Matthew O.; Weidner, Alison C.; Jayes, Friederike L.; Amundsen, Cindy L.; Gall, Ken; Miller, Andrew T.; Marini, Frank C.; Robboy, Stanley J.; Siddiqui, Nazema Y.
Abstract : Objective: Polycarbonate urethane (PCU) is a new biomaterial, and its mechanical properties can be tailored to match that of vaginal tissue. We aimed to determine whether vaginal host immune and extracellular matrix responses differ after PCU versus lightweight polypropylene (PP) mesh implantation. Methods: Hysterectomy and ovariectomy were performed on 24 Sprague-Dawley rats. Animals were divided into 3 groups: (1) PCU vaginal mesh, (2) PP vaginal mesh, and (3) sham controls. Vagina-mesh complexes or vaginas (controls) were excised 90 days after surgery. We quantified responses by comparing: (1) histomorphologic scoring of hematoxylin and eosin– and Masson trichrome–stained slides, (2) macrophage subsets (immunolabeling), (3) pro-inflammatory and anti-inflammatory cytokines (Luminex panel), (4) matrix metalloproteinase (MMP)-2 and -9 using an enzyme-linked immunosorbent assay, and (5) type I/III collagen using picrosirius red staining. Results: There was no difference in histomorphologic score between PCU and PP ( P = 0.211). Although the histomorphologic response was low surrounding all mesh fibers, groups with PCU and PP mesh had a higher histomorphologic score than the control group ( P < 0.005 and P < 0.002, respectively). There were no differences between groups in terms of macrophage subsets, pro-inflammatory cytokines, anti-inflammatory cytokines, MMP-2 and MMP-9, or collagen ratio. Conclusions: Polycarbonate urethane, an elastomer with material properties similar to those of vaginal tissue, elicits minimal host inflammatory responses in a rat model. Because its implantation does not elicit more inflammation than currently used lightweight PP, using PCU for prolapse mesh warrants further investigation with larger animal models.